Effects of 2,4-D , DMBQ and sorghum root extract on haustorium induction and attachment of witchweed [Striga hermonthica (Del.) Benth.] to roots of Sorghum bicolor (L.) Moench - Dafaallah, Awadallah B; Hamdoun, Abdalla M; Babiker, Abd Elgabar T (Gezira Journal of Agricultural Science; Vol 12 No 2 (2014), 2014)
Two types of experiments were conducted during 2006 in Wad Medani, Sudan in the laboratory. In vitro experiments were carried out to study the effects of 2,4-D at 2.5-100M, 2,6-dimethoxy-ρ-benzoquinone at 2.5 and 10.0 M and sorghum root extract at 6.3 and 25 g/L on haustorium induction of witchweed. In vivo experiments were carried out to study the effects of 2,4-D at 2,5-100M for pre-conditioning and soaking pre-conditioned witchweed seeds at the same rate for 10-120 min on attachment of haustorium to sorghum seedling roots. Treatments were arranged in a completely randomized design with three replicates. Witchweed germilings were examined for haustorium induction and attachment 4 and 15 days after treatment. Data were collected, transformed to arcsine as required and subjected to the analysis of variance procedure. The results revealed that haustorium induction and attachment to sorghum seedling roots was suppressed with increased 2,4-D concentration(2.5-100M) and soaking period (10-120 min) of pre-conditioned seeds. However, haustorium induction increased with increased 2,6-dimethoxy-ρ-benzoquinon (2.5 and10.0 M) and sorghum root extract concentration (6.3 and 25g/L). Much remains to be learnt about the action of 2,4-D. It appears to have a potential for Witchweed management. However, further research is needed to clear the basic principles of 2,4-D actions on Witchweed .       أجرى نوعان من التجارب المعملية خلال أبريل 2006 في واد مدني، السودان. أجريت التجربة الأولى لدراسة تأثير مبيد 2,4-D  بتركيز 2.5-100 مايكرومولر ومبدئ نشوء المماص (2,6-dimethoxy-ρ-benzoquinone)  بتركيز 2.5 و10 ميكرومولر ومستخلص جذور الذرة بتركيز 6.3 و 25 جم/لتر على نشوء مماص (Haustorium) طفيل البودا [ S . hermonthica (Del.) Benth.]. التجربة الثانية أجريت لدراسة تأثير مبيد 2,4-D بتركيز 20 أو 80 ميكرومولر لتهيئة بذور طفيل البودا ونقع البذور التي تمت تهيئتها في ذات التراكيز لمدة  10- 120 دقيقة على التصاق مماص الطفيل بجذور بادرة الذرة. وضعت المعاملات في تصميم عشوائي كامل بثلاث تكرارات. اختبرت بادرات البودا بغرض نشوء مماص والالتصاق بعد 4 و15 يوماً من المعاملة، على التوالي. جمعت البيانات حولت (arcsine) عند الحوجة، ثم أخضعت لتحليل التباين (ANOVA). تمت مقارنة المتوسطات بواسطة اختبار دنكن (DMRT)، عندما كان الاختبار معنوياً. أوضحت النتائج أنه انخفض تطور المماص والتصاقه بجذور بادرة الذرة بزيادة تركيز مبيد 2,4-D. إلاّ أن نشوء المماص ارتفع عند زيادة تركيز مبدئ نشوء المماص (2,6-dimethoxy-ρ-benzoquinone)  ومستخلص جذور الذرة.